Peningkatan Mutu Pelayanan Kesehatan Di Rumah Sakit Dengan Metode Six Sigma : Literature Review - Keren Stelin Maliangkay; Ummi Rahma; Safanny Putri; Acim Heri Iswanto (An-Najat, 2023)
High service quality is the most important factor to achieve optimal health service quality. The causes of low service quality include the influence of input factors, such as lack of infrastructure, finance, facilities, and human resources. Six sigma is used to improve quality, that contains a process of measurement, investigation, analysis, and evaluation. This study used the Systematic Literature Review (SLR) method or literature study. The secondary data used comes from literary sources in the form of scientific articles in Indonesian through an online site in the form of Google Scholar. Basically the principle of Six Sigma leads to improvement of results by making improvements to the process stages so as to produce a perfect product. Six Sigma is used to identify matters relating to errors or mistakes and to rework a product/service which in turn will spend more money and time. The success of implementing Six Sigma in an organization is measured based on the achieved sigma value. Based on the analysis conducted, it can be concluded that there has been an increase in the quality of health services in hospitals using the Six Sigma method. The application of the six sigma method has a significant impact on infection prevention and control in hospitals.